"Philosophy for Children e neuronarratologia": allenare il ragionamento abduttivo con il disegno sequenziale (Comparatismi, 2025)
After a long period of neglect within philosophical reflection, abduction began its rise in the late nineteenth century, thanks to Charles S. Peirce. Abduction has been reevaluated not only at the logical level, but also at the semiotic and interpretative levels, and in many other scientific fields. Furthermore, it has also been recognized as a fundamental cognitive process in everyday life. This paper presents and discusses the results of an experimental narratological study, part of the Philosophy for Children movement, which used sequential drawing to ‘train’ the ability to make abductive inferences. Along with abductive reasoning, some of the related skills such as causal inference, causal explanation and causal prediction were also stimulated.
Keywords: Philosophy for Children; Neuronarratology; Sequential drawing; Causal reasoning; Abduction